Spatial-temporal monitoring risk analysis and decision-making of COVID-19 distribution by region. (14th June 2022) - Pereira, Leandro; Correia, Jorge; Sequeiros, José; Santos, José; Jerónimo, Carlos
The purpose of this study is to model, map, and identify why some areas present a completely different dispersion pattern of COVID-19, as well as creating a risk model, composed of variables such as probability, susceptibility, danger, vulnerability, and potential damage, that characterises each of the defined regions. The model is based on a risk conceptual model proposed by Bachmann and Allgöwer in 2001, based on the wildfire terminology, analysing the spatial distribution. Additionally, a model based on population growth, chaotic maps, and turbulent flows is applied in the calculation of the variable probability, based on the work of Bonasera (2020). The results for the Portuguese case are promising, regarding the fitness of the said models and the outcome results of a conceptual model for the epidemiological risk assessment for the spread of coronavirus for each region.